Real-life vaccination coverage in Slovak children with rheumatic diseases - Balažiová, Barbora; Kuková, Zuzana; Mišíková, Daša; Novosedlíková, Katarína; Dallos, Tomáš (Frontiers in Pediatrics, 2022)
Background: Evidence-based recommendations for vaccination of patients with paediatric rheumatic diseases (PRDs) are available, their implementation in practice is unknown. Objectives: To analyse real-life vaccination coverage in children with PRDs and identify reasons for incomplete vaccination. Methods: Up-to-date information on vaccination status of Slovak children followed at a tertiary paediatric rheumatology centre was retrieved from paediatricians over an 18-month period and compared to the standard Slovak Immunisation Schedule. Reasons for missed vaccinations were analysed retrospectively. Results: Vaccination records of 156 patients (median age 10 years, 2-18) with PRDs (JIA n=108, systemic diseases n=21, autoinflammatory diseases n=16, uveitis n=9, others n=2) were available for analysis. 117 (75.0%) were completely vaccinated, 2 (1.3%) had not received any vaccine due to reasons unrelated to PRD. 37 (23.7%) remaining patients missed altogether 48 mandatory vaccinations. In 58.3% (n=28, in 24 patients) no PRD related reasons for missing vaccinations were identified. Only 20 vaccinations (18 live-attenuated and 2 non-live in 19 patients) were missed due to ongoing immunosuppressive treatment or PRD activity. Patients aged 11-14 years were more likely to be incompletely vaccinated than other age groups (48.8% vs. 15.9%, p<0.001), mainly due to missed MMR booster. Systemic immunosuppressive treatment was a significant predictor for incomplete vaccination status (OR 5.03, 95% CI 1.13-22.31, p=0.03). Conclusion: Full vaccination is possible in a high proportion of PRD patients. In addition to immunosuppressive therapy, reasons unrelated to PRDs are a frequent and possibly inadequate cause of missed vaccinations. Periodic vaccination status assessments are needed in paediatric rheumatology care.